Research progress of the role of intestinal microbiota-mediated bile acids in inflammatory bowel disease - XIA Xixi; DING Keke; ZHANG Huiheng; PENG Xufei; SUN Yimin; TANG Yajun; TANG Xiaofang (Shanghai Jiaotong Daxue xuebao. Yixue ban, 2024)
It is estimated that approximately seven million people worldwide are affected by inflammatory bowel disease (IBD), causing a huge burden on healthcare systems and society. In the occurrence, progression, and treatment of IBD, the intestinal microbiota and its key metabolic product, bile acids, play a crucial role. The intestinal microbiota not only participates in the biotransformation of bile acids, enriching the diversity of bile acids, but also regulates their synthesis and transport through the farnesoid X receptor (FXR). Meanwhile, bile acids contribute to regulating the structure and function of the intestinal microbiota by supporting microbial diversity, exerting direct toxicity, participating in indirect antimicrobial pathways, and influencing microbial metabolic capabilities. Furthermore, under normal physiological conditions, intestinal microbiota-derived bile acids facilitate the repair process of the intestinal epithelial barrier. They also promote the balance of the immune system by modulating the functions of various immune cells including helper T (Th) cells 17, regulatory T (Treg) cells, CD8+ T cells and natural killer T(NKT) cells, thereby slowing down the development of IBD. This article focuses on exploring the role of intestinal microbiota and bile acids in the onset and progression of IBD, and investigating new effective treatment strategies by targeting intestinal microbiota and bile acids, such as bile acid receptor modulators, probiotics, prebiotics, fecal microbiota transplantation (FMT), and phage therapy.